Politik Hukum Peraturan Bupati Nomor 63 Tahun 2016 Kabupaten Tulungagung Dalam Pengendalian Kerusakan Lingkungan Akibat Penambangan Pasir - Wakhid Ilham, Mohammad Roy; Rizal Fahlefi, Muhammad; fadli, Dzul (LPPM Universitas Ekasakti Padang, 2024)
Legal politics of regent regulation number 63 of 2016 Regency Tulungagung is involved in controlling environmental damage due to mining sand is a purposeful field study to answer the questions: 1. What is the Political Basis for Legal Regulations Regent Number 63 of 2016 Tulungagung Regency Under control Environmental Damage Due to Sand Mining and 2. What is the View Siyasah Syar'iyyah Fiqh on the Political and Legal Basis of Regent's Regulations Number 63 of 2016 Tulungagung Regency in Damage Control Environmental Effects of Sand Mining The type of research taken by the author is qualitative research with uses the nature of descriptive research, namely research directed at provide symptoms, facts or events systematically and accurate. The data sources used are primary and secondary data sources. Data Primary data is obtained from the results of analysis of statutory regulations related to research on legal political policy, regent's regulation number 63 2016 Tulungagung Regency in controlling environmental damage while secondary data from the research object is interviews, opinions of para experts in the form of books, journals and scientific works, as well as parties with related agencies. The results of this research show that legal political policy is regulatory regent number 63 of 2016 Tulungagung Regency in control environmental damage according to regent's regulation number 63 of 2016 is experiencing juridical defects and not implemented properly and do not meet standards AUPB, this is the first because there are two regulations that are the same where one of them should be removed and the contents of the implementation can be regulated more detailed and directed according to the rules above, but not here. So that In this case, the regulations alone are not appropriate, let alone the legal content where the Environmental Service should be able to take action against sand mining illegal and reclaiming environmental damage, but what is happening is not possible. that there is poor participation within the scope of correlation and regulation of the Tulungagung Regency government must be fixed immediately. Islam holds the view that it is an act of pollution The environment can be categorized as deep mafasid (damage). the principles of Islamic teachings must be avoided and overcome Regarding the solution, the author concludes that there must be firmness and role which is real for the Tulungagung Regency government, both executive and government legislative as well as improving regulations and repealing old rules with a view tidying up and strengthening the authority of the District Environmental Service Tulungagung through regent regulations